Combining visual and linguistic methods to cultivate and communicate river meanings with young children - Stephanie R. Januchowski‐Hartley; Ioanna Daphne Giannoulatou; Joelle Evans; Sian Howells (People and Nature)
Abstract Environmental education is a process that helps children and people of all ages to learn about environments and develop skills to address associated challenges. For early childhood environmental education, place‐ and arts‐based methods can raise children's awareness and appreciation of local environments by avoiding over‐reliance on scientific explanations. Opportunities exist for combining place‐ and arts‐based methods in environmental education to engage young people with local environments. Place‐based teaching intentionally leverages people's senses of place with emphasis on relationships to foster communication and engagement of broader concepts. Place‐ and arts‐based methods intersect in the exploration of relationality and can create space for children to participate in the construction and modification of place meanings based on their experiences or without having visited a place. In this article, we share a combined place‐ and arts‐based method to environmental education. Our approach centred on the creation of three visual media to raise river awareness with young children in Swansea, Wales, UK, and to encourage them to communicate about river places that have meaning to them. Educational activities that raise young children's awareness and encourages them to communicate about the meanings they hold for rivers can empower them to enact change. We chart the process of making and sharing Jac's River Adventure book and then give focus to a specific case that influenced our method and resulted in the creation of two additional visual media inspired by children's responses to Jac's River Adventure book. We discuss three key learnings from our creative and environmental education work, including that (1) tensions between fiction and non‐fiction can diversify pathways to environmental knowledge and nature connection; (2) anticipation of teacher enrichment and student engagement beyond initial environmental education activities is necessary; and (3) online environmental education for classrooms challenges relationship building. Our learnings highlight that combined place‐ and arts‐based methods have a role in environmental education and can foster awareness and communication about rivers through engagement and strengthening of local human/non‐human and human/human relationships. Read the free Plain Language Summary for this article on the Journal blog.